2002
DOI: 10.1590/s0004-282x2002000400009
|View full text |Cite
|
Sign up to set email alerts
|

Blink reflex: comparison of latency measurements in different human races

Abstract: -The blink reflex latencies and cephalometric indexes were analysed in 30 male volunteers from three different races, 10 white, 10 black, and 10 Oriental. Ages ranged from 15 to 59 years, height from 1,60 to 1,80 m, and weight from 60 to 80 kg. Blink reflexes were obtained after unilateral electric stimulation of the supraorbital nerve for quantitative analysis of 3 responses, early ipsilateral (R1), late ipsilateral (R2i) and late contralateral (R2c), obtained from the orbicularis oculi muscle. Cephalometric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
2
0
2
Order By: Relevance
“…Supraorbital stimulation-induced BR provides an early R1 component with a latency of approximately 10 ms, and a late R2 component with a latency of approximately 30 ms. 32,33 The upper limit of R1 latency was reportedly defined as 13 ms, and ipsilateral R2 latency should not exceed 40 ms. 34,35 In this study, nearly all the patients had normal latency in both R1 pre and R2 pre , except for two patients who were found to have a longer R1 pre (>13 ms) and one patient who had a longer R2 pre latency (>40 ms). The results of R1 pre and R2 pre were almost identical in the symptomatic side and asymptomatic side.…”
Section: Discussionmentioning
confidence: 99%
“…Supraorbital stimulation-induced BR provides an early R1 component with a latency of approximately 10 ms, and a late R2 component with a latency of approximately 30 ms. 32,33 The upper limit of R1 latency was reportedly defined as 13 ms, and ipsilateral R2 latency should not exceed 40 ms. 34,35 In this study, nearly all the patients had normal latency in both R1 pre and R2 pre , except for two patients who were found to have a longer R1 pre (>13 ms) and one patient who had a longer R2 pre latency (>40 ms). The results of R1 pre and R2 pre were almost identical in the symptomatic side and asymptomatic side.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic effects on ocular muscle morphology or peripheral nerve innervation have been proposed (Swerdlow et al, 2005), although one study found no difference between AA and EA in orbicularis oculi response to electrical stimulation (Kimaid, Resende, Castro, Berzin, & Barreira, 2002). While greater skin pigmentation has long been known to reduce skin conductance (Brown et al, 2006; Korol & Kane, 1978), it is not known whether the skin tone affects measured amplitude of the eyeblink component of the startle reflex in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…Neste estudo, resgatou-se conhecimentos básicos sobre a neurofi siologia do fenômeno de contração até a atrofi a. Denervação e envelhecimento das estruturas das fi bras musculares foram outros aspectos destacados [15][16][17][18][19][20] .…”
unclassified
“…O resultado, contudo, refere-se à manutenção da atividade neuromuscular mínima, que é o tônus muscular. Portanto, mesmo não existindo correlações clínica, eletromiográfi ca e morfológicas satisfatórias, o estudo detalhado de cada indivíduo com PF é essencial na decisão de eventual reabilitação 17,42,43 .…”
unclassified